Research and education to understand fire risks associated with dementia: A collaborative case study (innovative practice). (October 2020) - Heward, Michelle; Kelly, Fiona
This article reports on outcomes from the evaluation of a collaborative project between a University and a Fire and Rescue Service where research and education were developed to inform understanding of fire risks associated with dementia. Project outcomes were determined using a mixed-methods approach (survey, reports, statistics, case studies, course evaluation forms). Main outputs were a research report that identified dementia-specific fire risks and safety strategies, and an education package for Fire and Rescue Service staff and volunteers. The evaluation demonstrates the value of collaborative partnerships to develop understanding of risks pertinent to particular vulnerable groups and research-informed education.